2021
DOI: 10.7874/jao.2020.00269
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Deafness Due to Ischaemic Strokes in Both Temporal Lobes

Abstract: Cortical deafness is a clinical rarity whereby a patient is unresponsive to all types of sounds despite the preserved integrity of the peripheral hearing organs. In this study, we present a patient who suddenly lost his hearing following ischaemic infarcts in both temporal lobes with no other neurological deficits. The CT confirmed damage to the primary auditory cortex (Heschl's gyrus) of both hemispheres. Initially, the patient was unresponsive to all sounds, however, he regained some of the auditory abilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A cross-sectional study of 40 patients with dyslipidemia showed that higher triglyceride levels were associated with a higher average pure-tone threshold [ 29 ]. Suzuki et al showed that low levels of high-density lipoproteins were associated with atherosclerosis-related microcirculatory disturbances of the cochlear vasculature and increased susceptibility of the cochlea to noise, resulting in an increased risk of hearing loss [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study of 40 patients with dyslipidemia showed that higher triglyceride levels were associated with a higher average pure-tone threshold [ 29 ]. Suzuki et al showed that low levels of high-density lipoproteins were associated with atherosclerosis-related microcirculatory disturbances of the cochlear vasculature and increased susceptibility of the cochlea to noise, resulting in an increased risk of hearing loss [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 103 manuscripts was selected for a complete text evaluation, after which 44 were included [ 2 , 4 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The total number of patients included was 46 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The duration of the follow-up varied from 2 weeks to 15 years. A substantial part of the patients did not improve, and remained with a persistent inability to recognize any sound at all (16/34.8%) [ 2 , 8 , 12 , 15 , 16 , 17 , 18 , 19 , 29 , 33 , 34 , 35 , 37 , 43 , 46 , 48 ], while others evolved to pure word deafness (11/36.6%) [ 7 , 9 , 10 , 11 , 13 , 18 , 21 , 22 , 24 , 31 , 36 , 39 , 41 , 42 ]. Oral conversation was regained in six (20%) of the patients [ 7 , 20 , 25 , 27 , 28 , 32 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, central hearing loss involves disruption to the central auditory system -which begins with the auditory nerve exiting the cochlea and continues through to the auditory cortex of the brain (Zahnert, 2011). Central hearing loss and processing disorders of the central auditory system have many possible causes, including brain lesions (Jerger, 1987), meningitis infections (Kihara et al, 2012), brain injuries (Bergemalm and Lyxell, 2005;Oleksiak et al, 2012), strokes (Bamiou et al, 2012;Fujioka et al, 2020;Lachowska et al, 2021), multiple sclerosis (MS) (Matas et al, 2010;Valadbeigi et al, 2014), heavy metal poisoning (Dutra et al, 2010;Alvarenga et al, 2015;Castellanos, 2016), prenatal hypoxia (Jiang et al, 2008) and can also occur with age (Kim and Chung, 2013).…”
Section: Introduction 1problem Statementmentioning
confidence: 99%